1993
DOI: 10.2105/ajph.83.11.1616
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry and childhood mortality in northwest and southwest Uganda.

Abstract: Two longitudinal studies were carried out in northwest and southwest Uganda to examine the relationship between anthropometry and childhood mortality. Although the prevalence of malnutrition was significantly different between the two geographic areas, the relative risk for mortality associated with low levels of anthropometry was similar. When the anthropometric parameters were compared among each other, mid-upper arm circumference was found to be the most powerful predictor of mortality. The findings of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 7 publications
(2 reference statements)
0
40
0
Order By: Relevance
“…The arm measurements, in addition to the malnutrition markers, have proven to be good mortality predictors in population studies [21][22][23][24]. Compared with the BMI, the mid-arm muscle area circumference was a better mortality predictor in patients with chronic obstructive pulmonary disease [24].…”
Section: Anthropometrymentioning
confidence: 99%
“…The arm measurements, in addition to the malnutrition markers, have proven to be good mortality predictors in population studies [21][22][23][24]. Compared with the BMI, the mid-arm muscle area circumference was a better mortality predictor in patients with chronic obstructive pulmonary disease [24].…”
Section: Anthropometrymentioning
confidence: 99%
“…(1987) reached similarly equivocal conclusions. In Uganda, observations by Vella et al . (1993) implied that less than 20% of children identified as being at high risk of mortality through early measurement of arm circumference died during the follow‐up.…”
Section: Introductionmentioning
confidence: 97%
“…In Guinea-Bissau, Smedman et al (1987) reached similarly equivocal conclusions. In Uganda, observations by Vella et al (1993) implied that less than 20% of children identified as being at high risk of mortality through early measurement of arm circumference died during the follow-up. None of these studies were able to provide conclusive evidence that nutritional anthropometry would succeed in identifying children at high risk of morbidity, despite the policy importance of such an issue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] For children aged 0 to 60 months, WHO recommends using WFLz to define wasting, 15 since WFLz is a measure of undernutrition adjusted for height and therefore independent of stunting in its description of wasting. For any given anthropometric measure, a Z score indicates how many standard deviations below or above a reference median an individual value is found.…”
Section: Introductionmentioning
confidence: 99%